METALLOGENY OF THE MONT-DE-L’AIGLE IOCG DEPOSIT, GASPÉ PENINSULA, QUÉBEC, CANADA - Simard M.; Beaudoin G.; Bernard J.; Hupé A. (My University, 2006)
The Mont-de-l’Aigle deposit is located in the northern part of Dome Lemieux, in the Connecticut Valley-Gaspé Synclinorium, Gaspé Peninsula, Québec. The Dome Lemieux is a subcircular antiform of Siluro–Devonian sedimentary rocks that is cut by numerous mafic and felsic sills and dikes of Silurian to Late Devonian age. Plutonism occurred in a continental within-plate extensional setting typical of orogenic collapse. The Cu−Fe (± Au) mineralization of Mont-de-l’Aigle occurs in veins, stockworks, and breccias. Mineralization is located near or within N−S and NW−SE faults cutting sedimentary rocks. IOCG mineralization postdates intrusions, skarns, hornfels, and epithermal mineralization typical of the southern part of the Dome Lemieux. The paragenetic sequence comprises: (1) pervasive sodic, potassic, chlorite, and silica alteration, (2) hematite, quartz, pyrite, magnetite, and chalcopyrite veins, stockworks and breccias and, (3) dolomite ± hematite veins and veinlets cutting the earlier mineralization. Intrusions display proximal sodic and potassic alteration, whereas sedimentary rocks have proximal decalcification, silicification, and potassic alteration. Both intrusive and sedimentary rocks are affected by a pervasive distal chlorite (± silica) alteration. The sulfur isotope composition of pyrite and chalcopyrite (δ34S=−1.5 to 4.8‰) suggests that sulfur was derived mainly from igneous rocks. Fluid δ18O (−0.4 to 2.65‰) indicates meteoric or seawater that reacted with the country rocks. Mixing of hot magmatic fluids with a cooler fluid, perhaps meteoric or seawater is suggested for mineral deposition and alteration of the Mont-de-l’Aigle deposit. The mineralogy, alteration, and sulfur isotope composition of the Mont-de-l’Aigle deposit compare well with IOCG deposits worldwide, making the Mont-de-l’Aigle deposit a rare example of Paleozoic IOCG mineralization, formed at shallow depth, within a low metamorphic grade sedimentary rock sequence.
Keywords: GASPÉ PENINSULA; DOME LEMIEUX; IOCG DEPOSITS; HEMATITE; BRECCIA; Devonian; Silurian; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Silurian; Палеозой::Силурийская